Biodegradable Biomimetic Nanoplatform Orchestrating an Oxygen–Lactate Cascade to Enhance Photothermal Immunotherapy - Shuo Gao; Yu Chen; Yan‐Xi He; Cong‐Min Huo; Hui‐Yu Cen; Si‐Ye Tong; Rui Huang; Chen Luo; Houjuan Zhu; Wei Xue; Jing‐Yi Zhu (Advanced Healthcare Materials, 2026)
ABSTRACT A biodegradable biomimetic nanoplatform (HMCDL@TK‐M) was constructed by combining hydrogen‐doped H x MoO 3 nanoparticles, dual‐drug loading, and a hybrid spinach–cancer cell membrane coating. The system features pH‐responsive biodegradability, tumor‐homing capability, and high NIR‐II photothermal conversion. An oxygen–lactate cascade, formed via thylakoid membrane‐mediated H 2 O 2 decomposition and lactate oxidase‐driven lactate oxidation, alleviates hypoxia and depletes lactate in the tumor microenvironment. This dual metabolic modulation reprograms M2 macrophages to M1, promotes dendritic cell maturation, and reduces Treg infiltration. In 4T1 tumor‐bearing mice, HMCDL@TK‐M achieves strong tumor accumulation, effective photothermal ablation, and combined with lactate depletion, complete tumor eradication without systemic toxicity. The treatment also induces robust CD4 + /CD8 + effector memory T‐cell responses, providing durable antitumor immunity. This work demonstrates a synergistic metabolic–photothermal immunotherapy strategy for efficient and long‐lasting cancer treatment.